Ceratocystidaceae exhibit high levels of recombination at the mating-type (MAT) locus. Issue 12 (December 2018) - Simpson, Melissa C.; Coetzee, Martin P.A.; van der Nest, Magriet A.; Wingfield, Michael J.; Wingfield, Brenda D.
Abstract: Mating is central to many fungal life cycles and is controlled by genes at the mating-type ( MAT ) locus. These genes determine whether the fungus will be self-sterile (heterothallic) or self-fertile (homothallic). Species in the ascomycete family Ceratocystidaceae have different mating strategies, making them interesting to consider with regards to their MAT loci. The aim of this study was to compare the composition of the MAT locus flanking regions in 11 species of Ceratocystidaceae representing four genera. Genome assemblies for each species were examined to identify the MAT locus and determine the structure of the flanking regions. Large contigs containing the MAT locus were then functionally annotated and analysed for the presence of transposable elements. Genes typically flanking the MAT locus in sordariomycetes were found to be highly conserved in the Ceratocystidaceae . The different genera in the Ceratocystidaceae displayed little synteny outside of the immediate MAT locus flanking genes. Even though species of Ceratocystis did not show much synteny outside of the immediate MAT locus flanking genes, species of Huntiella and Endoconidiophora were comparatively syntenic. Due to the high number of transposable elements present in Ceratocystis MAT flanking regions, we hypothesise that Ceratocystis species may have undergone recombination in this region.